2021
DOI: 10.3390/min11050494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Operating Parameters on the Froth and Collection Zone Recovery in Flotation: An Industrial Case Study in a 10 m3 Cell

Abstract: The effects of flotation operation parameters, including froth depth, air flowrate, and frother dosage, on the froth and collection zone recovery and the flowrate of particles into the froth phase were investigated in a 10 m3 industrial cell. The results showed that froth recovery increases upon increasing air flowrate and frother dosage, as well as reducing froth depth. While all tested parameters affected the particles that entered into the froth phase, air flowrate and frother dosage showed the most and lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Because the bubbles that are coated with weaker particles burst faster (Ata, 2012;Wang et al, 2019) and as a result, they come out of this area through liquid drainage. It should be noted that the explained factors can affect the pulp zone as well (Ostadrahimi et al, 2021). It has been reported that higher air flowrate results in decreased bubble loading (Ostadrahimi et al, 2019), which leads to the formation of weaker bubbles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the bubbles that are coated with weaker particles burst faster (Ata, 2012;Wang et al, 2019) and as a result, they come out of this area through liquid drainage. It should be noted that the explained factors can affect the pulp zone as well (Ostadrahimi et al, 2021). It has been reported that higher air flowrate results in decreased bubble loading (Ostadrahimi et al, 2019), which leads to the formation of weaker bubbles.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the upper layer of the froth is usually dry in contrast to the lower area (Ata, 2012). Extensive studies have been performed on liquid drainage in two-phase foams (Pal and Masliyah, 1990;Neethling and Cilliers, 2002;Stevenson, 2006;Yianatos et al, 2018). Since mineral flotation contains large amounts of solid particles with different physical and chemical properties with high fluid content, theories have been developed that two-phase foam cannot be applied in understanding the flotation behaviour directly as solid properties affect the froth drainage dynamics (Ata, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In another work, the floatation of PET from the plastic mixture of PVC, polycarbonate (PC), and acrylonitrile–butadienestyrene copolymer (ABS) was efficiently achieved, modifying the hydrophilicity the PET surface by potassium hydroxide (KOH) and ethylene glycol ((CH 2 OH) 2 ) with the aid of sonication [ 17 ]. Significant efforts have been made by researchers to make the process efficient and economically attractive; furthermore, the rate at which plastic must be separated for the process has to be economically viable [ 18 , 19 , 20 ].…”
Section: Thermoplastic Polymersmentioning
confidence: 99%